Lighting the Way: Advances in Engineering Autoluminescent Plants. (December 2020) - Reuter, D. Nikki; Stewart, C. Neal; Lenaghan, Scott C.
Abstract : Until recently, robust autoluminescence in plants has proven elusive. Two recent pioneering manuscripts (Khakhar et al. and Mitiouchkina et al . ) expand our understanding of fungal bioluminescence to provide a new blueprint for engineering autoluminescence in plants. Here we discuss translating a fungal bioluminescence pathway into plants, along with potential future applications.